Peningkatan aktivitas dan hasil belajar fiqih pada materi wasiat melalui Penerapan Model pembelajaran problem posing siswa Kelas XI IPS-2 MAN 4 Bireuen - Khairiati, Khairiati (Universitas Serambi Mekkah, 2020)
The purpose of this study was to improve the activity and learning outcomes of Fiqh in the testamentary materials of students of class XI IPS-2 MAN 4 Bireuen. The model used in this study is the Problem Posing learning model. The subjects of this study were students of class XI IPS-2 MAN 4 Bireuen. The number of students is 32 students with 18 male students and 14 female students. This research was con-ducted in the 2017/2018 school year, within a period of 3 months, from February 2018 to April 2018 in the even semester. The methodology of this research is classroom action research consisting of two cy-cles and each cycle consists of two meetings. In each cycle consists of planning, implementation, obser-vation and reflection. The research procedure consisted of pre-research, planning cycle one, implement-ing cycle one, observing cycle one, reflection cycle one, planning cycle two, implementing cycle action two, observing cycle two and reflection cycle two. Data collection technique is to collect the value of the test carried out at the end of each learning in each cycle using the question instrument (written test). Ob-servation data is done by looking at the activeness of students in the learning process. Data were ana-lyzed by means of percentage statistics. The results showed that an increase in completeness of student learning outcomes from 37.50% in the pre-study increased to 62.50% in the first cycle and increased to 87.50% in the second cycle. Student learning activities have increased from enough categories to be good and good categories increased to very good. The application of the Problem Posing learning model can improve the activities and learning outcomes of Fiqh in the testament materials of students of class XI IPS-2 MAN 4 Bireuen 2017/2018 Academic Year.